Control de inventario de la “Empresa Agricola Briones Barragan Agribba S.A.” - provincia de Los Ríos, cantón Ventanas - Tapia Jiménez, Irene Isabel (2020)
This case study was carried out in order to describe the problems that arise in the inventory of Agrícola Briones Barragán AGRIBBA S.A. and aims to analyze the control of inventories used for the commercialization of the company, dedicated to the purchase and sale of agricultural products, such as fertilizers, seeds, agrochemicals, based on the high standards of quality and service. The main findings reflect that the company does not carry out the physical verification of the merchandise periodically and the disorganization of the products in the warehouse causes that the information obtained from the physical verification of the inventories is not reliable, this does not allow to make the appropriate decisions. The verification of the inventory at the end of the period and in intermediate periods should be one of the main strategies of the administrators for an effective control of the merchandise. The company is also exposed to risks that may affect it, as it does not have insurance for its inventories, due to fires, robberies, accidental losses or natural disasters. The inventory is important for small, medium and large companies as it is the fundamental factor for the profitability of the business.